DESIGN AND IMPLEMENTATION OF A PROJECT-BASED E-MODULE FOR HISTORY LEARNING TO FOSTER NATIONALISM: A STUDY AT SENIOR HIGH SCHOOL - Damasti Rohani Simanjuntak; Samsidar Tanjung; R.Mursid (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aimed to develop a Project-Based Learning-based e-module in history education to promote nationalism values among high school students. The research was conducted using the ADDIE development model, involving five phases: analysis, design, development, implementation, and evaluation. Data were collected through expert validation, student and teacher questionnaires, and pre- and post-tests with control and experimental groups. The feasibility of the e-module was validated by material, media, and instructional design experts, each indicating that the module was highly appropriate in terms of content accuracy, visual appeal, and instructional structure. Practicality tests with teachers and students revealed high usability and engagement levels. The results of the effectiveness test using an independent samples t-test showed a significant improvement in learning outcomes for students who used the e-module compared to those who used conventional textbooks. These findings confirm that the developed e-module is feasible, effective, and practical for use in history classrooms. It not only supports curriculum goals but also encourages active, independent learning and strengthens students’ national identity. The module holds strong potential for broader implementation and future development in digital history education.